Administrative Law Enforcement in Household Waste Sorting in Demak Regency - Aulia, Alifa (Law Research Review Quarterly, 2024)
Waste sorting is a process of waste management activities starting from the source starting from containers, collection, transportation, processing to disposal. One of the areas that has a waste problem is Demak Regency. The purpose of this study is to analyze related to administrative law enforcement in waste sorting in Demak Regency is carried out, so that interested parties achieve their goals or not and identify and analyze the factors that inhibit administrative law enforcement in household waste sorting in Demak Regency The research method uses a qualitative approach with the type of Empirical Juridical. Primary and secondary data sources were used in this study. Data collection was carried out through informant interviews, observations at the research site, and literature studies. The results of the study show: The implementation of administrative law enforcement in household waste sorting in Demak Regency has not been able to run optimally. The provision of administrative sanctions is the task of the Environmental Service which will be assisted by Satpol PP. The inhibiting factors of administrative law enforcement in household waste sorting in Demak Regency include the absence of a regent regulation regulating the procedures for sanctioning, the limited number of law enforcement officials, lack of facilities and infrastructure, and  the community's mindset that needs to be improved regarding the importance of separating waste from its source. Therefore, a Regent Regulation is needed that contains implementation instructions and technical instructions in the application of administrative sanctions in waste sorting. the existence of the Environmental Service in each district/city, improving facilities and infrastructure, and holding socialization about the importance of sorting waste from its source, namely households.